FILOSOFI DAN PENERAPAN KONSEPSI BUNGA PADMA DALAM PERWUJUDAN ARSITEKTUR TRADISIONAL BALI - Paramadhyaksa, I Nyoman Widya (Department of Architecture, Universitas Tanjungpura, 2016)
Padma adalah sebutan bunga teratai merah dalam bahasa Sanskerta. Padma tumbuh secara alami di media lumpur dengan kandungan air yang cukup. Akarnya tumbuh menjalar di media tanah, batangnya terendam di air, sedangkan daunnya yang lebar mengapung di permukaan air. Bunga padma yang sedang mekar berada di atas permukaan air, menengadah, bersih dari noda lumpur, dengan kelopaknya yang merekah sempurna ke segala arah. Karakter fisik padma yang sedemikian rupa ini telah lama melahirkan ilham dijadikannya padma sebagai bunga suci dalam ajaran Hindu dan Buddha. Dalam seni lukis dan seni arca timur, padma juga sering dijadikan lapik atau atribut yang digenggam tokoh dewa-dewi tertentu. Di Bali, padma juga dijadikan sebagai konsepsi dasar wujud bangunan suci dan arah mata angin. Kelopak-kelopak bunga padma yang merekah sempurna sering kali dikaitkan dengan keberadaan delapan arah mata angin utama yang diyakini dijaga oleh para dewata utama pula. Tulisan ini merupakan ringkasan dari suatu kajian yang menerapkan metode hermeneutik tentang filosofi bunga padma dan keterkaitannya dengan konsep arah mata angin utama yang dikenal dalam tatanan arsitektur tradisional Bali. Pada beberapa bagian juga akan dipaparkan gambaran wujud penerapan konsepsi bunga padma tersebut dalam berbagai perwujudan arsitektur tradisional Bali. Hasil akhir penelitian ini menunjukkan bahwa Konsepsi Padma ini telah terejawantahkan dalam tata ruang Pulau Bali, tata mandala pura, seni bangunan suci, dan seni ikonografis arca tradisional Bali.Â Padma refers to red water lily in Sanskrit. Padma grows naturally in the mud media with enough water content. Its roots spread in the soil planting media, the stem is submerged in water, while the leaves float on the water surface. Water lily flower blooms above the surface of the water, looking up, clean from mud, with petals that splitting all directions. Such padmaâ€™s physical characteristics have brought inspiration so that it becomes a sacred flower in Hinduism and Buddhism. In Eastern art, padma is often used as a pedestal or character attributes of certain gods or goddess. In Bali, padma serves as the basic concept of the sacred structure form and eight directions. The splitting petals of padma are often associated with the presence of the eight cardinal directions guarded by eight major gods. This paper is a summary of the study which applied the methods of philosophical hermeneutics on the philosophy of padma and its relevance to the concept of the main wind direction known in the order of traditional Balinese architecture. In some parts, it is also described the application description of Padma concept various embodiments of the Balinese traditional architecture. The final result of this research shows that Padma concept applied on Bali island masterplan, Hindu temple mandalas, holy buildings and iconographic of traditional Balinese sacred statues.REFERENCESAltman, Nathaniel (2002). Sacred Water: The Spiritual Source of Life. New Jersey: Paulist Press.Beer, Robert (2003). The Handbook of Tibetan Buddhist Symbols. Chicago: Serindia Publications, Inc.Debroy, Bibek dan Dipavali Debroy (2005). The History of Puranas. New Delhi: Bharatiya Kala Prakashan.Dwipayana, A. A. G. N. Ari dan Putra, I Nyoman Darma (2004). Bali Menuju Jagaditha: aneka perspektif. Denpasar: Pustaka Bali Post.Eiseman, Fred B. dan Margaret H. Eiseman (1989). Bali, Sekala and Niskala: Essays on religion, ritual, and art. Volume 1. London: Periplus Editions.Gupte, Ramesh Shankar (1980). Iconography of the Hindus, Buddhists, and Jains. Delhi: D. B. Taraporevala Sons.Heine-Geldern, Robert (1956). Conceptions of State and Kingship in Southeast Asia. New York: SEAP Publications.Kapur, Sohaila (1983). Witchcraft in Western India. New Delhi: Orient Longman.MacDonell, Arthur Anthony (1974). A Prctical Sanskrit Dictionary: with transliteration, accentuation, and etymological analysis throughout. London: Oxford University Press.Manuaba, Adnyana dan Supartha, Wayan (1999). Bali dan Masa Depannya. Denpasar: Penerbit Bali Post.Miksic, John N (1995). The Legacy of Majapahit. Singapore: National Heritage Board.Munandar, Agus Aris (2005). Istana Dewa Pulau Dewata: Makna Puri Bali Abad ke-14-19. Depok: Komunitas Bambu.Munandar, Agus Aris (2008). Ibukota Majapahit: Masa Jaya dan Pencapaian. Depok: Komunitas Bambu.Phalgunadi, I Gusti Putu (1991). Evolution of Hindu Culture in Bali: From the Earliest Period to the Present Time. Delhi: Sundeep Prakashan.Scheurleer, Pauline C. M. Lunsingh, dkk. (1988). Ancient Indonesian Bronzes: A Catalogue of the Exhibition in the Rijksmuseum Amsterdam with a General Introduction. Leiden: Brill Archive.Thompson, Richard L (2007). The Cosmology of the Bhagavata Purana: Mysteries of the Sacred Universe. Delhi: Motilal Banarsidass Publisher.Wiana, Ketut (2004). Mengapa Bali disebut Bali. Denpasar: Paramita